2019
DOI: 10.1186/s12861-019-0197-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of PRY-1/Axin in heterochronic miRNA-mediated seam cell development

Abstract: Background Caenorhabditis elegans seam cells serve as a good model to understand how genes and signaling pathways interact to control asymmetric cell fates. The stage-specific pattern of seam cell division is coordinated by a genetic network that includes WNT asymmetry pathway components WRM-1, LIT-1, and POP-1, as well as heterochronic microRNAs (miRNAs) and their downstream targets. Mutations in pry-1 , a negative regulator of WNT signaling that belongs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…The examination of animals carrying a nonsense mutation in pry-1, mu38, revealed an 80% reduction in the mean lifespan ( Figure 1C; Table S2). A similar phenotype is also observed in a CRISPR allele, gk3682, that deletes roughly 750 bp region including the 5' UTR and first exon (Mallick et al, 2019b) ( Figure 1C; Table S2). As pry-1 is also involved in developmental processes (Mallick et al, 2019a), we took an RNAi approach to knock down the gene function specifically during adulthood.…”
Section: Mutations In Pry-1 Reduce the Lifespansupporting
confidence: 64%
See 1 more Smart Citation
“…The examination of animals carrying a nonsense mutation in pry-1, mu38, revealed an 80% reduction in the mean lifespan ( Figure 1C; Table S2). A similar phenotype is also observed in a CRISPR allele, gk3682, that deletes roughly 750 bp region including the 5' UTR and first exon (Mallick et al, 2019b) ( Figure 1C; Table S2). As pry-1 is also involved in developmental processes (Mallick et al, 2019a), we took an RNAi approach to knock down the gene function specifically during adulthood.…”
Section: Mutations In Pry-1 Reduce the Lifespansupporting
confidence: 64%
“…Earlier, we reported both mRNA and microRNA (miRNA) transcriptome profiles of pry-1 mutant that revealed 2,665 differentially expressed (DE) proteincoding genes and six miRNAs (Mallick et al, 2019b;Ranawade et al, 2018). The characterization of DE genes revealed pry-1's role in miRNA-mediated seam cell development (Mallick et al, 2019b) and its novel function in lipid metabolism (Ranawade et al, 2018). In this study, we have specifically focused on the genes linked to aging.…”
Section: Pry-1 Transcriptome Contains Genes Involved In Lifespan Regumentioning
confidence: 99%
“…In support of its role in the asymmetric division of seam cells, pry-1 mutation disrupts the nuclear localization of WRM-1, SYS-1, and POP-1 [66,134,149], thereby leading to increased seam cell proliferation [65,66]. Work from our lab has shown that in the absence of PRY-1 function, POP-1 localization is disrupted in seam cell daughters [66]. As expected, RNAi knockdown of wrm-1 and lit-1 suppressed the seam cell phenotype in pry-1 mutants whereas pop-1 RNAi exacerbated the defect.…”
Section: Seam Cell Developmentmentioning
confidence: 99%
“…In addition to the above conserved WNT-mediated signaling events, studies in C. elegans have shown the presence of a divergent asymmetry pathway that regulates nuclear factor POP-1 in a WRM-1 (worm armadillo 1)/β-catenin-LIT-1 (loss of intestine 1)/NLK (Nemo-like kinase)-dependent manner (see [65] and references therein, [66]). In these cases, PRY-1 affects asymmetric POP-1 localization to control EMS (endomesodermal) precursor division in the embryo and seam cell divisions in larvae (discussed below).…”
Section: Axin Proteins Interact With Many Factors Including Signalingmentioning
confidence: 99%
See 1 more Smart Citation